Korelasi Shalat Dhuha Terhadap Kecerdasan Spiritual Siswa di MIM 12 Betiring Brondong Lamongan - Mushollin, Ahmad (STAI Muhammadiyah Paciran Lamongan, 2024)
The Correlation of Dhuha Prayers on the Spiritual Intelligence of Students at Mim 12 Betiring Brondong Lamongan for the 2022/2023 Academic Year. Thesis, S-1 Program of Islamic Religious Education Study Program, Paciran Muhammadiyah Islamic College, Lamongan. This research is motivated by the existence of problems in the rapid development of internet technology, namely the large number of shows through social media that no longer see the age limit and also the existing context, often conflict with religious and cultural values, resulting in a decline in ethics and also children's manners in life. every day because of the influence from the outside world that he sees. Not only that, deviations also occur in the norms of life, both religious and social. The purpose of this study was to determine the correlation of Duha prayer on the spiritual intelligence of students at MI Muhammadiyah 12 Betiring. Spiritual intelligence (Spiritual Quotient abbreviated as SQ) is intelligence to solve problems of meaning and value, namely intelligence to place behavior and life in the context of a broader and richer meaning, intelligence to judge that one's actions or way of life is more meaningful than others (Zohar , 2001: 12). The research method used in this study is a quantitative research method. Data collection techniques in this study were questionnaires and interviews. This research will be carried out by distributing questionnaires to MI Muhammadiyah 12 Betiring students. Data analysis will be carried out using a simple linear regression analysis method. The results showed that based on the analysis of hypothesis testing, either the F test or the T test, it was known that the conclusions of the two hypotheses were to reject H0 and accept Ha. This conclusion means that there is a significant and positive correlation simultaneously or partially with Duha prayer on the spiritual intelligence of students at MI Muhammadiyah 12 Betiring. The Coefficient of Determination also shows a very good number, which is 82.4%. The results of this study mean that the implementation and implementation of Duha prayer at MI Muhammadiyah 12 Betiring can achieve the desired goals and targets.